2001
DOI: 10.1590/s0100-879x2001001000002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of DDX26, a human DEAD-box RNA helicase, located on chromosome 7p12

Abstract: DEAD-box proteins comprise a family of ATP-dependent RNA helicases involved in several aspects of RNA metabolism. Here we report the characterization of the human DEAD-box RNA helicase DDX26. The gene is composed of 14 exons distributed over an extension of 8,123 bp of genomic sequence and encodes a transcript of 1.8 kb that is expressed in all tissues evaluated. The predicted amino acid sequence shows a high similarity to a yeast DEAD-box RNA helicase (Dbp9b) involved in ribosome biogenesis. The new helicase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Several studies have suggested that INTS6 plays tumor suppressive roles in several human cancers, such as non-small cell lung carcinoma, esophageal squamous cell carcinoma and prostate carcinoma [20-23, 31-34]. Mechanistically, INTS6 appears to induce Gap 1 (G1) arrest, explaining, in part its tumor suppressive roles in prostate cancer [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that INTS6 plays tumor suppressive roles in several human cancers, such as non-small cell lung carcinoma, esophageal squamous cell carcinoma and prostate carcinoma [20-23, 31-34]. Mechanistically, INTS6 appears to induce Gap 1 (G1) arrest, explaining, in part its tumor suppressive roles in prostate cancer [20].…”
Section: Discussionmentioning
confidence: 99%
“…The percent of nonredundancy is shown in relation to the cumulative number of sequences obtained for library F24I (squares), F33 (triangles), and H8-1 (circles). clusters that vary in size from 10 to 324 members (2). Unfortunately, there are only 1 4 000 S. mansoni EST sequences deposited in GenBank, and it would be difficult to determine if the modifications introduced here affect the ability of low-stringency RT-PCR to amplify rare S. mansoni messages.…”
Section: Normalization Of Cdna Libraries Obtained By the Modified Touchdown Method-estimates Using Human Cdnamentioning
confidence: 99%
“…In fact, despite the large set of more than 3.7 million EST sequences currently available from human tissues, it is apparent that only a fraction of the human gene complement has its full sequence determined. In this respect, a new low-stringency RT-PCR EST (ORESTES) sequencing strategy was shown to be complementary to other transcript sequencing strategies and to help determine the complete set of human expressed genes (2). A single arbitrary nondegenerate oligonucleotide primer is used both in the reverse transcription step and in the subsequent lowstringency PCR.…”
Section: Introductionmentioning
confidence: 99%